Interdisciplinarity in the Scholarly Life Cycle Learning by Example in Humanities and Social Science Research - Bijsterveld, Karin; Swinnen, Aagje (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book illustrates how interdisciplinary research develops over the lifetime of a scholar: not in a single project, but as an attitude that trickles down, or spirals up, into research. This book presents how interdisciplinary work has inspired shifts in how the contributors read, value concepts, critically combine methods, cope with knowledge hierarchies, write in style, and collaborate. Drawing on extensive examples from the humanities and social sciences, the editors and chapter authors show how they started, tried to open up, dealt with inconsistencies, had to adapt, and ultimately learned and grew as researchers. The book offers valuable insights into the conditions and complexities present for interdisciplinary research to be successful in an academic setting. Karin Bijsterveld is Full Professor of Science, Technology and Modern Culture at Maastricht University, the Netherlands. Her work focuses on themes at the intersection of science and technology studies and sound studies. She has taught extensively on how to do interdisciplinary research. Aagje Swinnen is Professor in Aging Studies at Maastricht University, the Netherlands. She has published on representations of aging in literature, photography, and film; meanings of literary approaches in dementia care; and ways in which professional artists understand and give meaning to creativity in the later stages of their career.